2012
DOI: 10.1088/0953-8984/24/35/354009
|View full text |Cite
|
Sign up to set email alerts
|

Charge transfer between isomer domains on n+-doped Si(111)-2 × 1: energetic stabilization

Abstract: Domains of different surface reconstruction -negatively-or positively-buckled isomershave been previously observed on highly n-doped Si(111)-2×1 surfaces by angle-resolved ultraviolet photoemission spectroscopy and scanning tunneling microscopy/spectroscopy. At low temperature, separate domains of the two isomer types are apparent in the data. It was argued in the prior work that the negative isomers have lower energy of their empty surface states than the positive isomers, providing a driving force for the fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…13 [42]. Interestingly, while positive buckling is the normally stable configuration, it has been found that negative-buckling regions may coexist with positive buckling at high electron concentrations [43,44], such as those present at our strongly accumulated surface.…”
Section: Possible Origins Of the Ll Contributionmentioning
confidence: 70%
“…13 [42]. Interestingly, while positive buckling is the normally stable configuration, it has been found that negative-buckling regions may coexist with positive buckling at high electron concentrations [43,44], such as those present at our strongly accumulated surface.…”
Section: Possible Origins Of the Ll Contributionmentioning
confidence: 70%
“…It is worth recalling that Ge(111) reconstructed surfaces, similarly to Si(111), display the symmetry described by the Pandey model, with surface chains running along the [0 11] crystallographic direction [13]. Buckling distortion of the chains is believed to explain the gap between dangling-bond states for both Si(111)-2 × 1 and Ge(111)-2 × 1 surfaces, as established by several consistent experimental and theoretical studies [9,[14][15][16][17][18][19][20][21]. The π -bonded chain model is also commonly accepted for the geometry of the reconstructed C(111)-2 × 1 surface [22,23], though some details of the relaxation (such as the presence of interchain dimerization, buckling at the surface atoms and deeper layer distortions) are not clear yet.…”
Section: Introductionmentioning
confidence: 78%
“…as well as at RT [18,19]. It has been argued that the relative abundances of the isomers depend on the size of the isomer domains and on the doping level due to a charge transfer between the domains [20]. For the two types of buckling, the relative positions of the surface bands in the band gap of bulk Si were determined by STS with high lateral resolution [19].…”
Section: Methodsmentioning
confidence: 99%